2021
DOI: 10.21203/rs.3.rs-355354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting CDK4 overcomes EMT-mediated tumor heterogeneity and therapeutic resistance in KRAS mutant lung cancer

Abstract: Lack of sustained response to therapeutic agents in patients with K-Ras mutant lung cancer poses a major challenge and arises partly due to intratumor heterogeneity that defines phenotypically distinct tumor subpopulations. To attain better therapeutic outcomes it is important to understand the differential therapeutic sensitivities of tumor cell subsets. Epithelial-to-mesenchymal transition (EMT) is a biologic phenomenon that can alter the phenotypic state and cause transcriptional rewiring to produce distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…These results indicated that KRT8 may exert its function by modulating cell migration and invasion in LUAD. Epithelial-to-mesenchymal transition (EMT) is a biologic phenomenon that can alter the state of cells along a phenotypic spectrum and cause transcriptional rewiring to produce distinct tumor cell subpopulations ( 25 ). It is reported that KRT8 can participate in cell migration and invasion through EMT ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that KRT8 may exert its function by modulating cell migration and invasion in LUAD. Epithelial-to-mesenchymal transition (EMT) is a biologic phenomenon that can alter the state of cells along a phenotypic spectrum and cause transcriptional rewiring to produce distinct tumor cell subpopulations ( 25 ). It is reported that KRT8 can participate in cell migration and invasion through EMT ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of inhibiting KRAS itself or the downstream MAPK pathway, EMT is blameworthy for drug resistance ( 45 ). Activation of the PI3K pathway in mesenchymal-like KRAS G12C mutant cancer cells could be the molecular basis for EMT-mediated resistance or, alternatively, could be due to a cell cycle alteration leading to CDK4-dependent growth ( 58 ). Cells expressing high levels of CSNK2A1 (Casein Kinase 2 Alpha 1) were found to have an increased mesenchymal gene signature, and reduction of CSNK2A1 converted the cells to the epithelial type and restored their sensitivity to KRAS G12C or MEK inhibitors ( 59 ).…”
Section: Non-genetic Adaptive Resistance Kras G12c ...mentioning
confidence: 99%